Dicobalt phosphide nanoparticles encased in boron and nitrogen co-doped graphitic layers as novel non-precious metal oxygen reduction electrocatalysts in alkaline media. Issue 81 (27th August 2015) - Han, Ce; Bo, Xiangjie; Zhang, Yufan; Li, Mian; Wang, Aixia; Guo, Liping
Abstract : Dicobalt phosphide nanoparticles encased in boron and nitrogen co-doped graphitic layers catalysts exhibited comparable ORR performance than the commercial Pt/C in alkaline solution with long term stability and excellent methanol tolerance. Abstract : Dicobalt phosphide nanoparticles encased in boron and nitrogen co-doped graphitic layers (BNC/Co2 P) were fabricated using a one-step pyrolysis method, which exhibited outstanding electrocatalytic ORR performance comparable to commercial Pt/C towards the oxygen reduction reaction via a four-electron pathway in alkaline solution with long-term stability and excellent methanol tolerance.